2005
DOI: 10.1039/b500398a
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of carbon monoxide on smaller gold-cluster anions in an atmospheric-pressure flow-reactor: temperature and humidity dependence

Abstract: In the absence of moisture and at room temperature, the activity and saturation of CO on gold cluster anions, Au(N)-, are known to be highly dependent on the size of the cluster. Small Au(N)- clusters (N = 2,3) showed no adsorption activity, and the saturation CO adsorption values did not increase proportionately to cluster size or area. Here, we report on the effects of water vapor and temperature on the ability of Au(N)- clusters to adsorb CO in a high-pressure, fast-flow reactor. In contrast to all earlier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…This contradicted Ervin's results that these small clusters react with CO, albeit slowly [273]. This was later explained when they reported that preadsorbed water on Au 2 À and Au 3 À allowed the subsequent adsorption of the carbonyl and displacement of water [278].…”
Section: Reactions Of Bare Gold Cluster Ions With a Single Substratementioning
confidence: 85%
See 1 more Smart Citation
“…This contradicted Ervin's results that these small clusters react with CO, albeit slowly [273]. This was later explained when they reported that preadsorbed water on Au 2 À and Au 3 À allowed the subsequent adsorption of the carbonyl and displacement of water [278].…”
Section: Reactions Of Bare Gold Cluster Ions With a Single Substratementioning
confidence: 85%
“…Wallace and Whetten have published several studies on the reaction of CO with size-selected gold clusters at room temperature [276,[278][279][280]. For instance, in a study aimed at understanding the size-dependent reactivity of Au x À (x ¼ 4-19) [280], they concluded that initial products formed seem to correspond mainly to clusters with a gold electron shell filling at 8, 14, 18 and 20 electrons (i.e.…”
Section: Reactions Of Bare Gold Cluster Ions With a Single Substratementioning
confidence: 99%
“…Gas-phase studies of isolated atomic clusters that can be considered as ideal models of active sites on related condensed-phase catalysts provide a unique approach to permeate the mechanistic details of elementary steps involved in the catalytic cycle. CO oxidation is one type of extensively studied reactions in the gas phase, while the studies are focused on the reactivity of bare metal clusters. , Available examples have emphasized the crucial roles of preadsorbed small molecules in promoting the reactivity of the resulting products in CO adsorption or oxidation. For example, the preattached CO was identified to modify the electronic structure of the Ni 2 VO 4 – cluster . The Ni 2 CO moiety that behaves like a noble-metal atom in the product Ni 2 VO 4 – [CO] is responsible for the storage of electrons during CO oxidation and drives the facile desorption of CO 2 .…”
Section: Introductionmentioning
confidence: 99%